Relação peso-comprimento e fator de condição de Salminus hilarii Valenciennes 1850 (Osteichthyes, Characidae) em um trecho da bacia do rio Sorocaba, Estado de São Paulo, Brasil - Villares Jr., Gilberto Aparecido [UNESP]; Gomiero, Leandro Muller [UNESP]; Goitein, Roberto [UNESP] (Universidade Estadual de Maringa, 2007)
The length-weight relationship and condition factor of Salminus hilarii were analyzed in a section of the lower part of the Sorocaba river basin, São Paulo State. By studying male, female and immature individuals separately, different length-weight patterns were found for each. The same happened when distinct seasonal variations of the relationships were compared, related to feeding alterations and to the reproductive period of the species.
Length-weight relationship and condition factor of Salminus hilarii Valenciennes 1850 (Osteichthyes, Characidae) in a section of the Sorocaba river basin, São Paulo State, Brazil
Keywords: Condition factor; Length-weight relationship; Salminus hilarii; Sorocaba river; Tabarana; body height; body weight; Brazil; feeding behavior; female; fish; geographic distribution; male; maturation; nonhuman; river; Salminus; seasonal variation; species identification; Characidae; Osteichthyes